Development of Mechanically Enhanced Polycaprolactone Composites by a Functionalized Titanate Nanofiller for Melt Electrowriting in 3D Printing - Pang, Le; Paxton, Naomi C; Ren, Jiongyu; Liu, Fan; Zhan, Haifei; Woodruff, Maria A; Bo, Arixin; Gu, Yuantong (ACS applied materials & interfaces, 2020)
Three-dimensional (3D) printing technologies are widely applied in various industries and research fields and are currently the subject of intensive investigation and development. However, high-performance materials that are suitable for 3D printing are still in short supply, which is a major limitation for 3D printing, particularly for biomedical applications. The physicochemical properties of single constituent materials may not be sufficient to meet the needs of modern biotechnology development and production. To enhance the materials’ performance and broaden their applications, this work designed and tested a series of titanate nanofiller (nanowire and nanotube)-enhanced polycaprolactone (PCL) composites that were 3D-printable and provided superior mechanical properties. By grafting two different functional groups (phenyl- and thiol-terminated ligands), the nanofiller surface showed improved hydrophobicity, which significantly improved their dispersion in the PCL matrix. After characterizing the surface modification, we evaluated the significance of the homogeneity of the ceramic nanofiller in terms of printability, formability, and mechanical strength. Melt electrowriting additive manufacturing was used to fabricate microfibers of PCL and PCL/nanofiller composites. Improved nanofiller dispersion enabled intact and uniform sample morphology, and in contrast, nanofiller aggregation greatly varied the viscosity during the printing process, which could result in poorly printed structures. Importantly, the modified ceramic/PCL composite delivered enhanced and stable mechanical properties, where its Young’s modulus was measured to be 1.67 GPa, which is more than 7 times higher compared to that of pristine PCL (0.22 GPa). Retaining the cell safety properties (comparable to PCL), the concept of enhancing biocompatible polymers with modified nanofillers shows great potential in the field of customized 3D printing for biomedicine.